Global Currency Wars: Implications for Emerging Economies - Angelov, Ivaylo (Journal of Environmental Science and Economics, 2023)
This paper examines the implications of global currency wars for emerging economies. Currency wars, defined as competitive devaluations of currencies by countries to boost their exports and economic growth, have become increasingly common in recent years. The impacts of currency wars on emerging economies are significant and multifaceted, including exchange rate volatility, inflation, trade imbalances, and capital flows. The paper analyzes case studies of Brazil, China, and India to illustrate the different responses of emerging economies to currency wars. The paper then discusses policy options for emerging economies, including exchange rate management, capital controls, monetary policy coordination, and regional cooperation. The paper concludes with a discussion of the future outlook for currency wars and their implications for emerging economies and offers policy recommendations for emerging economies to navigate this complex landscape.